Perencanaan luas produksi pada Perusahaan Tahu Putra Jaya di Kota Kupang - Tefa, Seprianus; Nyoko, Antonio E L; Foenay, Christien C (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the production area planning at the Putra Jaya Tofu Company in Kupang City. The research method used is using Trend Linear forecasting method and Break Even Point analysis. Based on the sales data for the last five years, it can be determined that the production area planning is obtained from the forecasting results and the Break Even Point analysis is carried out. The results showed that the company does not have a specific method in planning the area of ​​production. This has an impact on excess inventory or product residue which results in an increase in inventory costs. For the area of ​​tofu production at the Putra Jaya Tofu Company in Kupang City in 2020-2022, it has increased by 3% per year compared to the previous period. It is recommended for the Tahu Putra Jaya company to plan production area using the Trend Linear forecasting method and perform a Break Even Point analysis so that it is known that the production area planning experiences sales profits.